Experimental and numerical investigation of a Photovoltaic/Thermal/Phase Change Material System - Browne, Maria (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2016)
Hybrid Photovoltaic/Thermal (PV/T) systems generate both electricity and heat simultaneously. Typically 15 - 18 % of solar radiation incident on a PV module is converted to electricity and 82 - 85 % is converted to heat. This heat generated at the PV in a PV/T system is removed using a confined water or air flow. Phase change materials have been used extensively for thermal energy storage. At initial heating, a phase change material (PCM) heats sensibly and when the PCM reaches melting/solidification temperature the material absorbs latent heat, progressively melting. A novel Photovoltaic/Thermal/Phase Change Material (PV/T/PCM) system that generates electricity, stores heat and pre-heats wate is presented. The primary step involved in the design of the PV/T/PCM system was to select a PCM and containment material. An investigation into the characterisation of potential PCM using Differential Scanning Calorimetry and Temperature-History Method was carried out. Capric:palmitic acid was found to be most suited to integration in a PV/T/PCM system in Ireland. A long term corrosion study showed stainless steel to be intrinsically resistant to corrosion by PCM and for this reason it was a suitable PCM containment material.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; PhD Trinity College Dublin, 2016